2013
DOI: 10.1039/c3ra40745d
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of LixTiyOz thin films

Abstract: Atomic layer deposition (ALD) was employed to deposit ternary films of Li x Ti y O z. The film growth at a deposition temperature of 225 uC was studied using both titanium tetra-isoropoxide (Ti(O i Pr) 4) and titanium tetrachloride (TiCl 4) as titanium precursors. Lithium tert-butoxide (LiO t Bu) was applied as the lithium source and water was used as the oxygen source for all metal precursors. The type of titanium precursor chosen strongly affected film growth: with TiCl 4 the resulting Li x Ti y O z films we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…Carbon atoms are common impurities affecting the passivation quality of Al2O3 layers [5,7,8], and are considered harmful for surface passivation. Although ozone possesses a stronger oxidation potential than water, and has potentially beneficial effect on the reduction of impurity concentrations, as shown in previous studies [5,[8][9][10], other studies have also reported relatively high carbon concentration in ozone-based ALD films [11,12]. Despite this possible drawback, ozone-based ALD Al2O3 shows promising surface passivation quality [6,13].…”
Section: Introductionmentioning
confidence: 92%
“…Carbon atoms are common impurities affecting the passivation quality of Al2O3 layers [5,7,8], and are considered harmful for surface passivation. Although ozone possesses a stronger oxidation potential than water, and has potentially beneficial effect on the reduction of impurity concentrations, as shown in previous studies [5,[8][9][10], other studies have also reported relatively high carbon concentration in ozone-based ALD films [11,12]. Despite this possible drawback, ozone-based ALD Al2O3 shows promising surface passivation quality [6,13].…”
Section: Introductionmentioning
confidence: 92%
“…The films were amorphous as determined with X-ray diffraction and showed only very small amounts of lithium in ERDA measurements. In contrast, when using Ti(O i Pr) 4 as the titanium source and applying a long pulse time for this precursor, uniform titanate films with higher lithium contents could be deposited [99]. These films also reacted with air, however the reaction was much slower than when using TiCl 4 as the titanium precursor.…”
Section: Methodsmentioning
confidence: 91%
“…In both cases, LiO t Bu was used as the lithium source and water was used as the oxygen source. Titanate films deposited using TiCl 4 reacted rapidly in air [99]. The films were amorphous as determined with X-ray diffraction and showed only very small amounts of lithium in ERDA measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] For the case of conformal coatings, though, only a few publications demonstrating direct ALD of Li 4 Ti 5 O 12 are available. 18,19 Unfortunately, the electrochemical properties of these films were not tested. The ALD of complex oxides; i.e.…”
mentioning
confidence: 99%